The Role of Faculty and ICT Factors in Shaping Online Learning Experience: A Study Among Engineering Students - Pachava, Vengalarao; Golla, Siva Krishna; Vallabhaneni, Mounica (Journal of Engineering Education Transformations, 2025)
The present study investigates the influence of faculty-related and ICT-related variables on the overall online learning experience of students. The study involved the participation of 348 engineering students, and data analysis was carried out using a Chi-square Automatic Interaction Detector (CHAID) decision tree. The results of this research highlight the significance of delivering superior quality content and providing a designated learning environment, which can enhance students' level of satisfaction and involvement in online education. A positive correlation was observed between the employment of virtual laboratories and enhanced academic performance among students. The present research provides evidence for the impact of faculty engagement, the provision of suitable virtual learning environments, and the incorporation of online laboratory simulations in enhancing students' virtual learning encounters. The findings have noteworthy implications for educational institutions that aim to enhance student satisfaction and optimise online learning environments.